Vaccines and health and communication tools: analysis of the implicit association test - Martínez Martínez, Luz; Cuesta, Ubaldo; Bengoechea González, Carolina; Cuesta Díaz, Victoria (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
With the anti-vaccine movement, the perception of vaccines as neither safe nor effective is accentuated, influencing the perception and behavior of the population. Understanding the psychosocial mechanisms underlying the "anti-vaccine phenomenon" will allow the development of better intervention programs. This research pursues two objectives: 1) to analyze the Implicit Association Test (IAT) as a neurocommunication tool applied to communication and health, especially in vaccines, and 2) to understand the psychological mechanisms of the vaccine and anti-vaccine concept. The IAT is a useful tool although it presents certain methodological characteristics. There is a strong association of vaccines with health, responsibility and efficacy.